Pengaruh Budaya Kerja Dan Motivasi Berprestasi Terhadap Kinerja Aparatur Sipil Negara - Roni Bintara; Aldri Frinaldi (Universitas Teuku Umar, 2021)
In fact, there are still many negative assessments of the performance of the State Civil Servants. One of the factors that influence the performance of this State Civil Servant is the lack of a work culture that embodies achievement. Besides, the motivation of employee achievement also affects performance, because if the employee's motivation for achievement is high, the performance also will be high and it occurs on the contrary. Therefore, this research aims to know the effect of the work culture and motivation for achievement on the performance of the State Civil Servants at Bukittinggi Regional Ministry of Home Affairs Human Resource Development Center. This research was conducted on 65 employees using random sampling techniques. The results of the research indicated that the work culture and achievement motivation have a significant effect on performance at Bukittinggi Regional Ministry of Home Affairs Human Resource Development Center.